Penerapan ISAK 35 sebagai Strategi Meningkatkan Transparansi dan Akuntabilitas Laporan Keuangan pada Masjid Jami Ath-Thayyibah (Jurnal Riset Manajemen dan Akuntansi, 2025)
This study aims to analyze the implementation of the Interpretation of Financial Accounting Standards (ISAK) 35 in the financial reporting of Masjid Jami’ Ath-Thayyibah as an effort to improve transparency and accountability in religious non-profit organizations. A descriptive qualitative approach was employed through observations, interviews, and document analysis. The findings reveal that the mosque’s financial reports are still limited to simple records of cash inflows and outflows and do not yet comply with the five key components required by ISAK 35. The main challenge identified is the limited understanding and technical skills of the personnel responsible for financial reporting. However, the mosque management has shown a willingness to improve the quality of reporting if provided with proper training and technical assistance. These findings highlight the importance of external support and capacity building in implementing standardized financial reporting in community-based mosques.